Development of a critical thinking assessment instrument based on Dieng's local context - Fadilah, Solikhah Isti; Sriyati, Siti; Amprasto, Amprasto; Irawan, Tb Moh Irma Ari (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2026)
Critical thinking is a crucial core competency in biology education; however, authentic assessments that integrate local wisdom remain limited. This study addresses the need for a valid and reliable critical thinking assessment instrument based on the local context of Dieng. An exploratory sequential mixed-method design was employed, encompassing stages of qualitative exploration, instrument development, expert validation, readability testing, and field trials. The limited trials were conducted on two groups consisting of 31 and 32 students, respectively, followed by a large-scale trial involving 201 senior high school students. Quantitative data were analyzed using the Rasch model with Winsteps version 3.73 to examine item validity, reliability, and unidimensionality. The qualitative findings identified four forms of local wisdom and fifteen local potentials of Dieng that were relevant to biology learning in Phases E and F of the Merdeka Curriculum. The Rasch analysis showed that the developed instrument demonstrated excellent item reliability (0.96) and acceptable unidimensionality (21.7%). In conclusion, this study successfully developed a psychometrically valid critical thinking assessment instrument that integrated Dieng local wisdom as an authentic context in biology learning. The instrument met validity and reliability criteria and was suitable for measuring students’ critical thinking skills in a contextual and meaningful manner.